Penatalaksanaan Teknik Pemeriksaan Fistulografi Dengan Klinis Fistula Perianal Di Instalasi Radiologi Rumah Sakit X - Danil Hulmansyah; Pratiwi Mutiara Zanisman; Devi Purnamasari (LPPM POLBITRADA, 2024)
The fistulography examination is a radiology examination that uses iodine-based contrast to visualize the condition and opening of the fistula duct. The frequent indications for this examination are perianal fistulas, using several examination projections, namely plain film projection, AP axial, AP oblique, prone/lateral, axial Chassard-Lapine method, and Taylor. This examination is carried out using a fluoroscopy machine. The purpose of this study is to determine the management and radiographic results of the fistulography examination technique with perianal fistula clinics. The type of research used is a descriptive qualitative case study approach. The data collection methods are observation, interviews, and documentation. The research was conducted at the Radiology Installation of X Hospital from March - June 2022. The subjects in the study were 2 Radiographers and 2 Radiology Specialist Doctors with the research object being the management of the fistulography examination technique with perianal fistula clinics. The results of this study indicate that the fistulography examination with perianal fistula clinics does not require any special preparation, the patient only needs to remove any metal objects that may interfere with the radiographic results and change into the patient gown provided. The projections used are plain film, AP axial, AP oblique, prone and lateral. The fistulography examination using these projections is able to provide optimal results by showing the contrast media entering through the fistula duct, so there is no need to use other projections.